2016
DOI: 10.1080/23273798.2015.1130234
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of similarity in the mental lexicon

Abstract: During language production planning, multiple candidate representations are implicitly activated prior to articulation. Lexical representations that are phonologically related to the target (phonological neighbors) are known to influence phonetic properties of the target word. However, the question of which dimensions of phonological similarity contribute to such lexical-phonetic effects remains unanswered. In the present study, we reanalyze phonetic data from a previous study, examining the contrasting predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
7
15
0
Order By: Relevance
“…Moreover, producing these sequences is associated with increased rates of speech errors (O’Seaghdha & Marin, 2000; Sevald & Dell, 1994), longer production latencies, and slowed down speech rates (for review, see Jaeger, Furth, & Hilliard, 2012a). Increased competition is assumed to result in hyper-articulation, offering a potential explanation for Competitor effects, such as the ones observed here and in similar previous studies (Baese-Berk & Goldrick, 2009; Goldrick et al, 2013; Kirov & Wilson, 2013; see also Fox, Reilly, & Blumstein, 2015; Fricke, Baese-Berk, & Goldrick, 2016; Peramunage, Blumstein, Myers, Goldrick, & Baese-Berk, 2011). …”
Section: Discussionsupporting
confidence: 78%
“…Moreover, producing these sequences is associated with increased rates of speech errors (O’Seaghdha & Marin, 2000; Sevald & Dell, 1994), longer production latencies, and slowed down speech rates (for review, see Jaeger, Furth, & Hilliard, 2012a). Increased competition is assumed to result in hyper-articulation, offering a potential explanation for Competitor effects, such as the ones observed here and in similar previous studies (Baese-Berk & Goldrick, 2009; Goldrick et al, 2013; Kirov & Wilson, 2013; see also Fox, Reilly, & Blumstein, 2015; Fricke, Baese-Berk, & Goldrick, 2016; Peramunage, Blumstein, Myers, Goldrick, & Baese-Berk, 2011). …”
Section: Discussionsupporting
confidence: 78%
“…A number of experimental and observational studies have reported that competition at the lexical level is correlated with hyperarticulation of phonetic properties in the target word. This correlation has been reported for English in a number of studies investigating the realization of vowel formants (e.g., Wright, 1997;2004;Munson & Solomon, 2004;Munson, 2007;Scarborough, 2012), vowel durations (Schertz, 2013;Seyfarth, Buz, & Jaeger, 2016; but see Goldrick, Vaughn, & Murphy, 2013), degree of coarticulation (Scarborough, 2012(Scarborough, , 2013, perseveration of voicing in coda fricatives (Seyfarth et al, 2016;Kharlamov, 2014), and initial stop voice onset time (Baese-Berk & Goldrick, 2009;Peramunage et al, 2011;Kirov & Wilson, 2012;Schertz, 2013;Fricke, 2013;Buz, Tanenhaus, & Jaeger, 2016;Fox, Reilly, & Blumstein, 2015;Fricke, Baese-Berk, & Goldrick, 2016). In each of these cases, some form of lexical competition has been found to correlate with hyperarticulation of phonetic properties of individual segments (e.g., Wright, 2004;Fricke, 2013;; but see Goldrick et al, 2013;Gahl, 2015).…”
Section: Introductionsupporting
confidence: 57%
“…For example, Fricke's (2013) Articulate As Soon As Possible Principle (AASAPP) posits that articulation unfolds on a segment-by-segment basis, and begins as soon as competition in a given segmental position is resolved. According to this model, the relative position of difference between the target and its competitors is therefore of paramount importance, but the phonetic relationships among those competitors is not relevant -a greater number of competitors defined for a particular segmental position leads to increased activation of the target segment regardless of phonetic relationship (Fricke, 2013; see also Vitevitch, Ambrüster, & Chu, 2004;Fricke et al, 2016). In contrast, both communicative and listenerinternal accounts are based on perceptual confusability, such that hyperarticulation is targeted to those cues that maximize perceptual distinctiveness between competitors.…”
Section: The Phonetic Specificity Of Competitionmentioning
confidence: 99%
See 2 more Smart Citations